Tomato ( Lycopersicon esculentum ) prevents lead-induced testicular toxicity - Emmanuel O Salawu; Olusola A Adeeyo; Olutunde P Falokun; Uthman A Yusuf; Abiodun Oyerinde; Anthony A Adeleke (Wolters Kluwer Medknow Publications, 2009)
Background: Lead, an example of heavy metals, has, for decades, being known for its adverse effects on various body organs and systems such that their functions are compromised. Aim: In the present study, the ability of lead to adversely affect the male reproductive system was investigated and tomato ( Lycopersicon esculentum : Source of antioxidants) paste (TP) was administered orally to prevent the adverse effects of Pb. Materials and Methods: Fifteen Sprague Dawley rats, randomised into three groups (n = 5), were used for this study. Animals in Group A served as the control and were drinking distilled water. Animals in Groups B and C were drinking 1% Pb (II) acetate (LA). Group C animals were, in addition to drinking LA, treated with 1.5 ml of TP/day. All treatments were for 8 weeks. Statistical Analysis Used: A Mann-Whitney U -test was used to analyse the results obtained. Results: The obtained results showed that Pb caused a significant reduction in the testicular weight, sperm count, life-death ratio, sperm motility, normal sperm morphology, and plasma and tissue superoxide dismutase and catalase activity, but a significant increase in plasma and tissue malondialdehyde concentration. But, Pb did not cause any significant change in the serum testosterone level. TP, however, significantly reduced these adverse effects of Pb. Conclusion: These findings lead to the conclusion that TP significantly lowered the adverse effects of Pb exposure on the kidney as well as Pb-induced oxidative stress.